Musée imaginaire: Fontanes Gemäldegalerie - Fischer, Hubertus (Studia Germanica Posnaniensia, 2017)
This paper tends to explore ,Fontane's picture gallery' referring to its genesis, characteristic and effect. In doing so the art critic Fontane is improving a distinctive image as an expert especially of English art und of the at that time in Germany leading Dusseldorf School of Painting (Düsseldorfer Malerschule). Furthermore it will be set out how the writer Fontane is acting in his work with pictures and pictorial perception. Eventually there is a suggestion for recovering ,Fontane's picture gallery' to make it possible for the contemporary audience to read Fontane's works in a wider and subtly differentiated manner.